Nucleic Acid Drugs for Preventing Restenosis after Coronary Revascularization - Miyake, Takashi; Nakagami, Hironori; Morishita, Ryuichi (Current Topics in Medicinal Chemistry, 2012)
Recent progress in molecular and cellular biology has resulted in the development of numerous effective drugs. However, there are still a number of diseases for which no known effective therapy exists, such as ischemic heart disease, vascular bypass graft failure and heart failure. Despite its limitations, oligodeoxynucleotide (ODN)-based therapy is emerging as a potential strategy for the treatment of patients with cardiovascular disease that is resistant to current therapeutic approaches. Indeed, several nucleic acid drugs and delivery methods for heart disease have been developed and their efficacy has been investigated in animal models. Among them, some agents have undergone clinical trials, such as cmyc antisense ODN, E2F and NFκB decoy ODN. However, none of the large randomized placebo-controlled trials has shown conclusive evidence of clinical benefit. Recent experimental studies suggested that siRNA- and miRNA-based strategies have potential as a potent therapeutic approach for the treatment of restenosis. In addition, simultaneous regulation of multiple intracellular signaling pathways is expected to enhance the therapeutic effects. This review focuses on the potential of recent ODN-based gene therapy for the treatment of heart disease, especially restenosis after revascularization.
Keywords: ODN-based gene therapy